CCR7 Sulfotyrosine Enhances CCL21 Binding - Andrew J. Phillips (International Journal of Molecular Sciences, 2017)
Chemokines are secreted proteins that direct the migration of immune cells and are involved in numerous disease states. For example, CCL21 (CC chemokine ligand 21) and CCL19 (CC chemokine ligand 19) recruit antigen-presenting dendritic cells and naïve T-cells to the lymph nodes and are thought to play a role in lymph node metastasis of CCR7 (CC chemokine receptor 7)-expressing cancer cells. For many chemokine receptors, N-terminal posttranslational modifications, particularly the sulfation of tyrosine residues, increases the affinity for chemokine ligands and may contribute to receptor ligand bias. Chemokine sulfotyrosine (sY) binding sites are also potential targets for drug development. In light of the structural similarity between sulfotyrosine and phosphotyrosine (pY), the interactions of CCL21 with peptide fragments of CCR7 containing tyrosine, pY, or sY were compared using protein NMR (nuclear magnetic resonance) spectroscopy in this study. Various N-terminal CCR7 peptides maintain binding site specificity with Y8-, pY8-, or sY8-containing peptides binding near the α-helix, while Y17-, pY17-, and sY17-containing peptides bind near the N-loop and β3-stand of CCL21. All modified CCR7 peptides showed enhanced binding affinity to CCL21, with sY having the largest effect.